Microbial mitigation of stress response of food legumes - Amaresan, N.; Murugesan, Senthilkumar; Kumar, Krishna; Sankaranarayanan, A. (Boca Raton, FL : CRC Press LLC, 2020)
Microbial Mitigation of Stress Responses of Food Legumes provides knowledge on the impact of abiotic and biotic stress on the agriculture of grain legumes especially pulses and it critically reviews the cutting-edge research in exploring plant microbe interactions to mitigate the stress. It helps in understanding the fundamentals of microbial-mediated management of abiotic and biotic stress in grain legumes. Salient features: Describes the usefulness of microbiome of plant/insects for enhancing the production of grain legumes Focuses on recent advances in microbial methods for mitigating the stress and their application in sustainability of legume production Provides a unique collection of microbial data for the improvement of legume productivity Details microbial metabolites at the gene and molecule levels for plant stress management The reader will get all essential and updated information on various stress factors, crop responses, and microbial-mediated stress management for better food legume production.
17: Bacterial Biological Control Agents for Soilborne Diseases Management in Pulses: Present Status and Future Prospects -- 18: Bacillus thuringiensis Cry Gene Mediated Biological Pest Management in Grain Legumes -- 19: Structural and Functional Diversity of Cry Genes and Their Utilization in Pest Management of Grain Legumes -- 20: Microbial Mitigation of Biotic Stresses in Soybean (Glycine max) -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Legumes -- Effect of stress on; Plant-microbe relationships; Food -- Microbiology; Legumes as food; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General; TECHNOLOGY / Agriculture / General